(untitled) (Crossing the Border: International Journal of Interdisciplinary Studies, 2017)
The aim of this paper is to provide a discursive analysis of the phenomenon of squatting in Nepal. The paper begins by charting the concept of discourse from its inception as an analytic framework in Bakhtin’s theory of discourse to more recent application in tracking regimes of power, including international developments. The paper then examines the discourse of representation and praxis characterizing government and urban planning approaches to squatting in Nepal, followed by two case studies conducted in Chapagaun that illustrate the manner in which power circulates in a Nepali squatter settlement as well as in the lives of individual squatters. The paper concludes by arguing that the resources which fuel the praxis of squatting (e.g. finances, political connections and knowledge) often exclude the very people most in need of land and housing through disarticulation, or the omission of local voices. Crossing the Border: International Journal of Interdisciplinary Studies Vol.4(1) 2016: 3-18